Smoking Dependence and Cardiovascular Endurance in Late Adolescents: A Study at the Faculty of Engineering, Udayana University - Ambarita, Ester Yolanda; Antari, Ni Komang Ayu Juni; Wahyuni, Nila; Pramita, Indah (Majalah Ilmiah Fisioterapi Indonesia; Vol 13 No 2 (2025): Majalah Ilmiah Fisioterapi Indonesia, 2025)
Introduction : Cardiovascular endurance is influenced by various factors, one of which is smoking habits, which can hinder oxygen binding by hemoglobin. Additionally, smoking is a leading cause of cardiovascular disease-related deaths worldwide. This study aims to identify the relationship between smoking dependence levels and cardiovascular endurance in late adolescents at the Faculty of Engineering, Udayana University. Methods : This cross-sectional study employed a simple random sampling method from June to September 2024. Sixty-five students from the Faculty of Engineering, Udayana University, who met the inclusion and exclusion criteria, participated in the study. Cardiovascular endurance was assessed using the Harvard Step Test while smoking dependence levels were measured using the Fagerström Nicotine Dependence Test (FTND). Data were analyzed using Spearman’s rho correlation test. Results : A moderate negative correlation was found between smoking dependence levels and cardiovascular endurance (r = -0.503, p = 0.001), indicating that higher smoking dependence is associated with lower cardiovascular endurance. Conclusion : Smoking dependence has a negative relationship with cardiovascular endurance in late adolescents. This study has limitations, including a limited sample size and excluding other lifestyle factors, such as diet and physical activity, which may also influence cardiovascular endurance. Keywords : smoking, dependence, cardiovascular, adolescents